Optimization of fractional crystallization on crude biodiesel purification via response surface methodology - Samsuri, S. (Taylor and Francis Inc., 2018)
In order to improve separation and purification efficiency of biodiesel, an alternative method has been explored which is fractional crystallization. In this study, glycerol that has a higher melting point was formed as a solid phase while the pure biodiesel was remained in liquid phase during the crystallization process. Response surface methodology (RSM) and central composite design (CCD) were employed to search for the optimum operating conditions. The best responses were 0.117 and 46.734 for effective partition constant (K) and concentration efficiency (Eff), respectively, while the optimum operating conditions were coolant temperature at â9.5Â°C and stirring rate at 362 rpm. Â© 2017 Taylor & Francis.